PENGARUH GREEN MARKETING DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI KOTA MATARAM - Fermatika Oktavia Hanna; Ahmad Fatoni Karim Amirullah; I Ketut Kusuma Wijaya (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the influence of green marketing and lifestyle on the purchasing decisions of The Body Shop products in Mataram City. The method used is quantitative with a survey approach, involving 100 respondents selected through purposive sampling techniques. Data were collected using a questionnaire measuring the variables of green marketing, lifestyle, and purchasing decisions with a Likert scale. Data analysis was conducted using multiple linear regression, showing that green marketing and lifestyle have a positive and significant effect on purchasing decisions. The results indicate an R-Square value of 0.65, meaning that 65% of the variance in purchasing decisions can be explained by these two variables. These findings suggest that marketing strategies focused on sustainability and promoting an environmentally friendly lifestyle can enhance consumer loyalty to The Body Shop products